A soil column study to evaluate treatment of trace elements from saline industrial wastewater - Paredez, Jose M.; Mladenov, Natalie; Galkaduwa, Madhubhashini B.; Hettiarachchi, Ganga M.; Kluitenberg, Gerard J.; Hutchinson, Stacy L. (My University, 2017)
Industrial wastewater from the flue gas desulfurization (FGD) process is characterized by the presence of trace elements of concern, such as selenium (Se) and boron (B) and relatively high salinity. To simulate treatment that FGD wastewater undergoes during transport through soils in subsurface treatment systems, a column study (140-d duration) was conducted with native Kansas soil and saline FGD wastewater, containing high Se and B concentrations (170 ?g/L Se and 5.3 mg/L B) and negligible arsenic (As) concentration (?1.2 ?g/L As). Se, B, and As, and dissolved organic carbon concentrations and organic matter spectroscopic properties were measured in the influent and outflow. Influent Se concentrations were reduced by only ?half in all treatments, and results suggest that Se sorption was inhibited by high salinity of the FGD wastewater. By contrast, relative concentrations (C/Co) of B in the outflow were typically <10%, suggesting that B sequestration may have been enhanced by higher salinity. Unexpected elevated As concentrations in the outflow (at >150 ?g/L in the treatment with labile organic carbon addition) suggest that soils not previously known to be geogenic arsenic sources have the potential to release As to groundwater in the presence of high salinity wastewater and under reducing conditions.
Citation: Paredez, J. M., Mladenov, N., Galkaduwa, M. B., Hettiarachchi, G. M., Kluitenberg, G. J., & Hutchinson, S. L. (2017). A soil column study to evaluate treatment of trace elements from saline industrial wastewater. Water Science and Technology. https://doi.org/10.2166/wst.2017.413
Keywords: Arsenic; Boron; Constructed wetlands; Flue gas desulfurization; Fluorescence; Selenium